The Impact of Transition and Economic Integration on Manufacturing Employment Change: An Assessment for the Regions of the European Union New Member-States - Dimitrios Kallioras (European Regional Science Association (ERSA), 2006)
The spatial and structural dynamics generated (or released) in the contexts of the parallel and interacting processes of transition and economic integration have already left a clear mark in the economic landscape of the EU new member-states. The paper re-evaluates the experience of these countries with respect to shifts in their territorial structures and balances since despite the increasing portion of transition-integration literature many parameters remain of limited research. The analysis is conducted at the NUTS III spatial level on the basis of manufacturing data according to NACE classification for the period 1991-2000. This is a period of extreme importance since it includes both the shocks and the upsets of the early transition and the more recent trends of the pre-accession period. The analysis focuses on the manufacturing sector due to its significance in the former politico-economic regime and due to the high pressures that this sector has encountered afterwards. Regional-industrial data limitations restrict the analysis in the regions of Bulgaria, Romania, Hungary, Estonia and Slovenia. These regions still constitute a highly heterogeneous group since areas with different economic, demographic and geographic characteristics are represented. The trade-adjusted shift-share analysis, an extension of traditional shift-share analysis, is performed in order to evaluate the impact of transition and economic integration on regional manufacturing employment change. Despite its non-theoretical character, the method allows for valuable results to be drawn on the issue.
Keywords: 330